Product Scarcity Appeals, Social Media Promotion, and Impulse Buying: Evidence from Cadbury ENHYPEN Edition - Amelia Resa Salsabila; Arus Reka Prasetia (Jurnal Wacana Ekonomi, 2026)
Limited edition collaborations between fast-moving consumer goods brands and K-pop idols have reshaped how young consumers respond to scarcity cues and digital promotional content. This study examines the influence of product scarcity appeals and social media promotion on impulse buying toward Cadbury ENHYPEN Edition among K-pop consumers in Bandung. Using a quantitative survey design, primary data were collected through a structured questionnaire from respondents selected through purposive sampling. The data were analyzed using multiple linear regression after instrument quality and classical assumption testing. The findings show that product scarcity appeals have a positive and significant relationship with impulse buying. Social media promotion also has a positive and significant relationship with impulse buying and emerges as the stronger predictor in the regression model. Jointly, both predictors explain 67.2 percent of the variance in impulse buying. The Stimulus-Organism-Response framework is used as an interpretive lens rather than a fully tested model because internal psychological states were not measured directly and no mediation pathway was examined. The study contributes to consumer behavior literature by integrating scarcity appeals, social media promotion, and fandom-based symbolic consumption in a limited edition FMCG context.